COMMUNITY EMPOWERMENT BASED ON SOCIAL ENTREPRENEURSHIP TRAINING: TRAINING IN MANAGEMENT OF COFFEE LEATHER BROWNIES BUSINESS IN SOPPENG CITY, SOUTH SULAWESI - Amin, Nur; Prakaswati, Tingga Sari Novi; Khotimah, Husnul; Sumarto, Iin (Islamic Economics Program, Faculty of Islamic Economics and Business, 2019)
The purpose of this study was to determine the level of success of the implementation of social entrepreneurship-based community empowerment programs in the training of business management of coffee skin brownies in Soppeng City, South Sulawesi. The population of this study was all people who participated in entrepreneurship training in the community empowerment program as many as 285 people. Data was collected using a questionnaire instrument that was processed and analyzed using quantitative descriptive analysis. The results showed that the level of success of the implementation of social entrepreneurship training-based empowerment programs in Soppeng City was highly measured by indicators: (1) increased knowledge and skills of the community in managing coffee skin into brownies, preparing business/business plans, and making simple books; (2) increasing community participation in training programs; and (3) increasing interest in the community in developing social-based creative entrepreneurship